Metal fixing plates for plate osteosynthesis: understanding choice — clear choice - Richter, Oleksandr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2009)
The article is an excursion into the history of the appearance of the idea of development of functional stable osteosynthesis. An evolutional way of changes in the demands to the type of stability depending upon the injury complexity is elucidated. Advantages and disadvantages of all kinds of metal fixing plates, available on the Ukrainian market, are shown with the purpose to help every doctor examine and understand abilities and the area of application of different metal fixing plates for improving the quality of medical aid with an individual approach to every patient.